Effectiveness Of Eco Farming Photosynthesis Fertilizer and Goat Manure Fertilizer on The Vegetative Growth of Coffee Plant Seedlings (Coffea Sp) - Yudi Siswanto; Isnar Sumartono; Djodi Kurniawan (Yayasan Sinergi Multidimensi Kreatif, 2024)
Effectiveness of Eco Farming Photosynthesis Fertilizer and Goat Manure Fertilizer on Vegetative Growth of Coffee Plants (Coffea sp) The purpose of this study is to determine the effectiveness of the application of photosynthetic eco farming fertilizer and goat manure fertilizer and its interaction on the vegetative growth of coffee plants (Coffea sp), This research was carried out from November 2023 to February 2024 in Sei Mencirim Village, Sunggal District, Deli Serdang Regency, North Sumatra Province. The study used the Factorial Group Random Design (RAK) method with two treatment factors, the first factor is photosynthetic eco farming fertilizer consisting of 4 levels, namely E0 = 0 ml/liter of water/plot, E1 = 100 ml/liter of water/plot, E2 = 200 ml/liter of water/plot, E3 = 300 ml/liter of water/plot, while the second factor is goat manure fertilizer which consists of 4 levels, namely K0 = 0 g/plot, K1 = 100 g/plot, K2 = 200 g/plot, and K3 = 300 g/plot. The parameters observed were plant height (cm), number of leaves (strands), and stem diameter (mm). The results showed that the effectiveness of applying photosynthetic eco farming fertilizer and goat manure fertilizer had an effect on plant height (cm), stem diameter (mm), and the number of leaves (strands) of coffee plant seedlings. The interaction of the effectiveness of the application of photosynthetic eco farming fertilizer and goat manure fertilizer did not affect the plant height (cm), stem diameter (mm), and the number of leaves (strands) of coffee plant seedlings.